Effect of COVID-19 Lockdown on the Investment and Profitability in Crop Enterprises: A Cross-sectional Evidences from Uttar Pradesh (Indian Journal of Extension Education, 2023)
Study was conducted among 570 farmers spreading across 57 districts of Uttar Pradesh during the period of 25 March to 10 May 2020 by telephonic contact using the pre structured interview schedule to assess the effect of COVID-19 lockdown on the investment and profitability of major rabi crops of the state namely wheat, mustard, lentil, chickpea, and field pea. The effect was ascertained by comparing the lockdown status with the same period (March-May) of last year (2019). Findings showed that though the price of production inputs increased during the lockdown, albeit the variation in price jump was not very high. On the profitability front, wheat and lentil growers remained the most affected as compared to mustard, field pea, and chickpea growers. The production cost was affected more as compared to the market price of these commodities. The increased production cost was attributed to increased inputs cost due to the limited opening of input outlets despite the state Government’s instruction for relaxation in complete lockdown to agricultural inputs shops in the state of Uttar Pradesh. KVK experts also opined that the COVID lockdown restricted the movement of farm labourers and inputs availability which adversely affected the farm sector of the state.